(3aJGhi SCd YfgG TjN GdMLGR LeGd GdOjf GHf XgjQg hGdELGHI YdjgGs - (3SQGL GdOjf GdHdbjfjs
(3ChdgG (B:s
(3CeG HYO agPg eSGFd SFd YfgG YGde GdMLGR LdGd GdOjf Hf XgjQg dTjN GdGSdGe SQGL GdOjf GdHdbjfi QMeg Gddg GdChdi ZPG bdfG HeG bGdg GdZRGdi ef Jhdjg GdbVGA ef SdWGf Pi ThcI aGSbkG s
(3BNQgG (B:s
(3hCMGd Ydi TQMI ddHNGQi ai GdOdjd Ydi JaVjd NOjLI Ydi YGFTI hCeG HbjfI fSeGFg aHbjI HfGJg GaVd hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1221s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3Gdabg GdESdGejs